A Performance Study of “Care Compagne...Come per me serene": A Comparison of scores published by Ricordi and Schirmer / Nor Lydazura Ab Aziz - Ab Aziz, Nor Lydazura (2009)
This thesis is about A performance study of " Care Compagne...per me sereno": A comparison of score published by Ricordi and Schirmer. Basically this report consists of five chapters which start with Introduction. This chapter sets the background of study, problem statement, research objective, research question and also significance of research. The research problems for this investigation come when I get confused about the differences betoveen score Ricordi and Schirmer. This found this score at the library and my major objective is to determine which score is more appropriate to use as a materials for study and also teaching. I have analysed several comparison to detect the appropriate score. In completing this research, I used primary sources which are qualitative approach and also my major method is secondary sources which include books, scores and also articles. Besides that, I also used a recording as my minor references to compile this thesis. Then on second chapter I focus on the literature review. This section includes a fully referenced review and discussion of previous studies which is relevant to the research. There is having five books have been review in this chapter. Through .this investigation there is have 4 books as my references in completing this task. It is More Than Singing (The interpretation of Song) by Lotte Lehmann), Koloratura Arien (Sopran) by Mathilde De Castrone Marchesi, Coloratura Arias For Soprano by Robert L. Larsen and Martha Gerhart, and Musical Performance (A Guide to Understanding) by John Rink. The most useful books towards my research are the books by John Rink in title Musical Performance (A guide to understanding). In chapter four the findings of this study shows that most of the comparison have their own significant and can contribute to my self and also other performer. This section provides the result and analysis of data. The results obtained can be presented as a series of figures; tables with descriptive text and discussion. Before the comparison, I do analysis score from Ricordi and also Schirmer.